2000
DOI: 10.1016/s0014-5793(00)02223-7
|View full text |Cite
|
Sign up to set email alerts
|

RAC‐3 is a NF‐κB coactivator

Abstract: It has been shown that the molecular mechanism by which cytokines and glucocorticoids mutually antagonize their functions involves a mutual glucocorticoid receptor (GR)/nuclear factor-U UB (NF-U UB) transrepression. Here we report a role for the nuclear receptor coactivator RAC3, in modulating NF-U UB transactivation. We found that RAC3 functions as a coactivator by binding to the active form of NF-U UB and that overexpression of RAC3 restores GR-dependent transcription neglecting GR/ NF-U UB transrepression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
122
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(136 citation statements)
references
References 37 publications
(51 reference statements)
13
122
1
Order By: Relevance
“…The absence of a protective effect in cells untransfected with the expression vector for the co-activator was presumably due to the essentially undetectable levels of endogenous RAC3 co-activator, at least for the protein quantity that was used in western blot assays (Figure 2f). This is in agreement with the concept that limiting quantities of p160 co-activators are present in non-tumoral cells (Sheppard et al, 1998;Werbajh et al, 2000). In addition, this figure clearly shows increased expression levels of RAC3 in cells transiently transfected with the expression vector and the resulting inhibition by siRNA compared to extracts from transfected control cells overexpressing RAC3 as well as the breast tumor T47D cell line.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The absence of a protective effect in cells untransfected with the expression vector for the co-activator was presumably due to the essentially undetectable levels of endogenous RAC3 co-activator, at least for the protein quantity that was used in western blot assays (Figure 2f). This is in agreement with the concept that limiting quantities of p160 co-activators are present in non-tumoral cells (Sheppard et al, 1998;Werbajh et al, 2000). In addition, this figure clearly shows increased expression levels of RAC3 in cells transiently transfected with the expression vector and the resulting inhibition by siRNA compared to extracts from transfected control cells overexpressing RAC3 as well as the breast tumor T47D cell line.…”
Section: Resultssupporting
confidence: 90%
“…As previously described in other cell lines (Werbajh et al, 2000), we observed that RAC3 overexpression significantly enhanced H 2 O 2 -induced NF-kB transcriptional activity in HEK293 cells as compared to cells transfected with empty vector (Figure 3a). These results raise the possibility that an increase in the transcription of anti-apoptotic NF-kB target genes could represent a mechanism by which overexpression of the RAC3 co-activator protects cells from cell death.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations